Rotary Evaporator Design And Equipment Performance To Increase The Concentration Of Moringa Leaf Extract - Bagus Pratama, Wisnu; Parida Hutapea, Henny; Ambarwati, Septiana (Proceeding of the International Conference Health, Science And Technology (ICOHETECH), 2024)
The process of extracting active compounds from Moringa leaves requires efficient techniques so that active compounds can be isolated in high concentrations without damaging the chemical structure. The tool commonly used is a rotary evaporator. This research analyzes the percentage of solvent evaporation using a Rotavap Extractor and a conventional rotary evaporator. Both tools aim to maximize solvent evaporation by retaining active compounds from the extract. This research compares the effectiveness of the two tools based on the percentage of solvent evaporated and the viscosity of Moringa leaf extract with different time variations (40, 60, 80 minutes). The percentage of solvent that evaporates has an important role in determining the concentration and viscosity of Moringa leaf extract. As more solvent evaporates, the extract becomes more concentrated, increasing the viscosity due to the high concentration of active compounds. The percentage of solvent evaporated and viscosity show the same trend between the conventional rotary evaporator and the rotavap extractor, this indicates that both devices work with similar efficiency in evaporating solvent from Moringa leaf extract.